Prevalence and Predictors of Physical and Sexual Violence among Women in Nepal (Journal of Tikapur Multiple Campus, 2025)
This article analyses the incidence and factors associated with physical and sexual violence against women in the age group of 15–49 years in Nepal, based on the Nepal Demographic and Health Survey 2022. Despite the increase in the literature, it is justified that violence affects the well-being and socio-economic development of people in many areas globally. This paper incorporates demographic factors which are explained from both the social and the feminist theoretical perspectives. In the present study, based on the cross-sectional data, the factors including age, marital status, education, wealth and the region were established as significant logistic regression analysis predictors. The sample was selected from women aged between 15 and 49 years old, and methods of stratification and weighting were followed to make the sample more representative. The findings suggest 22.5 percent women faced physical violence starting from the age of 15 and 7.5 percent women reported lifetime sexual violence. Older women aged 35 and above years old and women who have been divorced, separated or widowed were at a higher risk. Female survivors of violence were 4.29 [CI 3.67– 4.98] times more likely to experience physical violence. The comparison of different regions equally revealed that the Madhesh province was more experiencing higher levels of violence, education and wealth influencing violence in that the lower level of education and lower level of wealth was positively associated to violence. Community level responses should cover the cost and educational aspects of tackling the effects of violence.